The Influence of Communication Leadership and Workload on Employee Performance at the Banyudono District Office, Boyolali Regency - Vanesa*, Paulina Ria; Wijiastuti, Sri; Widodo, Zandra Dwanita (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research aims to determine the influence of (1) Leadership (2) Communication (3) Workload on Employee Performance at the Banyudono District Office, both partially and simultaneously. Thisresearch is quantitative using primary and secondary data. Data quality analysis testing uses validity tests and reliability tests. This research uses a survey method by distributing questionnaires. From a population of 30 people, all were sampled using saturated sampling techniques. The analysis used is multiple linear regression. This research shows that leadership partially influences employee performance by 25.6%. Communication partially influences employee performance by 46.1%. Workload fiber partially influences employee performance by 23.1%. Leadership, communication, and workload simultaneously or together also have an influence on employee performance, shown by a significant value of 0.000 0.05. Meanwhile, the coefficient of determination test results have an Adjusted R Square value of 89.5%, which means that employee performance variables are influenced by leadership, communication and workload variables and the remaining 10.5% is influenced by other variables.